Rhythm of the woods - Khng, Qian Ci (2018)
Rhythm of the Woods, celebrates the cyclical balance of Mother Nature through the activities of little forest animals. It is Lighthearted and simple. Inspired by Yusuke Oono’s 360° book, the film brings the pages to life through animation. The causal sequence of the actions of the little woodland animals resonates with Nature. The 360° concept of coming back in a full natural cycle - starting and ending with the same animal - portrays the connection to Nature’s rhythms, and realigning life and daily habits with the cycles of the universe.